Islamic Contracts of Finance in Malaysia - Matt Richards (Studia Islamika, 2003)
This paper explores the legal issues that arise in several of the principal instruments currently used in Islamic financing in Malaysia. Through the document review, it is submitted that these financial instruments consist of English-Malaysian commercial law, albeit set within an Islamic periphery. A consideration of how Islamic law could affect the litigation of these instruments is also undertaken and it is further submitted that given the current statutory and judicial framework of Islamic banking in Malaysia, the effect of Islamic commercial law upon these contracts appears to be morally exhortative, rather than legally enforceable. Finally, it is concluded that Islamic law is presently consigned to the margins of these financial contracts, and the consequences that arise from this conclusion are discussed.DOI: 10.15408/sdi.v10i1.641